Multi‐objective optimisation design of a suspension‐guided permanent magnet synchronous linear motor for ropeless elevator - Xu, Xiaozhuo; Zhang, Yangyang; Feng, Haichao; Zhao, Yunji; Zhou, Menglin (IET electric power applications, 2023)
In this article, a suspension‐guided permanent magnet synchronous linear motor (SG‐PMSLM) for ropeless elevator is proposed, which can meet the requirements of high thrust and high thrust density for ropeless elevator, and reduce vibration noise and wheel‐rail wear during motor operation. The structure, working principle and electromagnetic characteristics of SG‐PMSLM are analysed. In order to improve the overall performance of SG‐PMSLM, this article aims at improving the average thrust and thrust density, reducing the thrust fluctuation of SG‐PMSLM. Firstly, the sensitivity analysis of the key structural parameters of SG‐PMSLM is conducted, and the parameters that have significant influence on the three optimisation objectives are selected as the optimisation variables. Secondly, the response surface model of three optimisation objectives is built, and the Particle Swarm Optimisation algorithm is combined to conduct the multi‐objective optimisation design for SG‐PMSLM. Thirdly, the optimised solution set is obtained for three objectives. Finite Element Analysis is used to verify that the optimised solution set has better diversity and can effectively improve SG‐PMSLM overall performance compared with the initial design. Finally, the electromagnetic performance of SG‐PMSLM is verified by experiments.